Penyebab dan Resistensi Kegalauan pada Remaja Pacaran (Studi Kasus di Desa Pandan Indah Kabupaten Lombok Tengah) - Rohimi, Rohimi (Tazkir : Jurnal Penelitian Ilmu-ilmu Sosial dan Keislaman, 2021)
Dating has become a part of social phenomena in society. Dating is indeed a way to strengthen the closeness between men and women. But in dating, it is not always smooth, but someone can experience breakups, fights, and so on. Therefore. This study examines the causes and resistance of anxiety in dating adolescents who experience a breakup or fight with their partners. This research was conducted in Pandan Indah Village, Praya Barat Daya District, Central Lombok Regency, using a qualitative approach or field research. The data collection methods used in this study were interviews, documentation and observation, with the aim of knowing the causes and resistance of anxiety in dating adolescents in Pandan Indah Village, Praya Barat Daya District, Central Lombok Regency. The results and discussion in this study are. First, the phenomenon of the teenage dating culture in Pandan Indah Village which is still thick or fanatical with their dating culture, namely midang, where midang is the arrival of a man to his girlfriend's house which is only carried out at night with certain purposes such as strengthening his relationship, building solidarity or closeness. the families of both parties, then to discuss their future wedding day. Second, the causes of turmoil in dating relationships in Pandan Indah Village include dishonest couples, lack of communication and cheating partners. Third, the resistance of turmoil in dating relationships in Pandan Indah Village, namely such as calming down in the room, doing spirituality such as reciting and praying, and calming their gala feelings by listening to music.